2020
DOI: 10.3390/f11010054
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Effects of Thinning on the Leaf C:N:P Stoichiometry of Regenerated Broadleaved Trees in Larch Plantations

Abstract: The shift from natural mixed broadleaved forests to pure coniferous plantations results in soil degradation and the unsustainable development of plantations due to the simple stand structure and low species diversity. Thinning can practically sustain the forest structure and promote the regeneration and growth of broadleaved trees in these pure coniferous plantations. The growth of regenerated broadleaved trees is closely related to leaf ecological stoichiometry, which is strongly restricted by environmental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Our results were consistent with earlier reports, and further supported our findings to some extent. Moreover, lower C:N and C:P ratios in stems and leaves showed that the lowest nutrient use efficiency and growth rate may occur under shading conditions [18]. The higher C:N and C:P ratios were observed in leaves under moderate shading conditions, indicating that a higher C:N or C:P ratio accumulated in seedlings [2].…”
Section: Effects Of Shading Treatments and Soil Types On Growth Perfo...mentioning
confidence: 95%
See 1 more Smart Citation
“…Our results were consistent with earlier reports, and further supported our findings to some extent. Moreover, lower C:N and C:P ratios in stems and leaves showed that the lowest nutrient use efficiency and growth rate may occur under shading conditions [18]. The higher C:N and C:P ratios were observed in leaves under moderate shading conditions, indicating that a higher C:N or C:P ratio accumulated in seedlings [2].…”
Section: Effects Of Shading Treatments and Soil Types On Growth Perfo...mentioning
confidence: 95%
“…Although plants may adapt to many soil types, the growth, biomass allocation, root architecture, nutrient absorption, and physiological characteristics are directly or indirectly affected by the differences in soil types [16,17]. Earlier studies showed that under low nitrogen (N) and low phosphorus (P) conditions, the ratios of C:N and C:P in leaves of plants are lower, resulting in more efficient nutrient utilization efficiency [18]. Moreover, nutrients are more easily absorbed in fertile, moist, and well-drained loam, which improves seedlings growth and development in some plants [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Photographs were taken with Canon 6D and Canon 8-15 mm f/4L USM hemispherical lens. Images were processed by the Gap Light Analyzer Software (Sun et al 2016;Xie et al 2020). The relevant results are shown in Additional file 1: Fig.…”
Section: Seedling Emergence Survival and Growth In The Fieldmentioning
confidence: 99%
“…In the long-term evolution process, plants have formed a series of mechanisms and strategies to adapt to the changing environment. One of the important, nutrient resorption is important for nutrient recycling and reuse under the pressures of resource crisis caused by environmental changes and the need for a stable balance of nutrients to maintain the normal physiological activities of plants (Sterner and Elser, 2002;Fan et al, 2015;Xie et al, 2020;Li et al, 2021), thus increasing the chances of plant survival and species continuation (Zhao et al, 2006). Nutrient resorption is the transfer and transport of nutrients to other tissues of plants before senescence and litterfall (Killingbeck, 1986;Aerts, 1996;Lu et al, 2018); it provides energy and nutrients for new tissues and prolongs the retention time of nutrients in plants, thereby reducing the process of plant dependence on external nutrients (Covelo et al, 2008;Zhao et al, 2010;Vergutz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%